Experimental investigation of air characteristics during dehumidification in the multilayer desiccant bed column system - Prueksa Sawardsuk; Jiraporn Sripinyowanich Jongyingcharoen; Ekkapong Cheevitsopon (My University, 2018)
The gold of this research is to investigate air characteristics during dehumidification process using the multilayer desiccant bed. Silica gel packing in the multilayer column was used as a desiccant material. Airflow direction in the column was designed in a zigzag path passing each desiccant layer. The changes in temperature and relative humidity of exit air were recorded after dehumidification at different airflow rates of 18, 36, and 72 m 3 /h. In the desiccant regeneration process, moisture in silica gel was removed by 85°C of hot air at varied airflow rates. The characteristics of exit air after regeneration were also monitored. The result revealed that air humidity ratio was significantly decreased using multilayer desiccant bed column. The highest rates of air dehumidification and desiccant regeneration were observed in the first 5 min operation. The highest air dehumidification rate was 12.82 g/min at the airflow rate of 72 m 3 /h and the highest regeneration rate of desiccant was 6.70 g/min at the airflow rate of 72 m 3 /h. In addition, the dual column of multilayer desiccant bed can be successfully applied to cyclic operation of dehumidification and regeneration when the cycle time were 5 min and airflow rate 36 and 72 m 3 /h.
Keywords: Adsorption and Cooling Systems